Determinants of household income of micro-finance women participants: a quantile regression approach - Duasa, Jarita; Zainal, Nur Hidayah (Emerald Publishing, 2020)
Purpose – The purpose of this study is to adopt quantile regression to investigate the impact of several factors on per capita income of participants of micro-financing scheme (Amanah Ikhtiar Malaysia [AIM]), who are mostly women at different point on the income distributions. Design/methodology/approach – This study uses data collected from a survey on respondents who are the participants of AIM program using convenience sampling in Perak and Kelantan. Findings – The empirical results show that the value of asset, value of loan, household size, ratio of spending to income and dummy state are consistently giving similar impacts on per capita income of participants at different quantiles. Originality/value – However, age negatively and significantly affects per capita income only at middle and lower quantiles but not at higher quantile of per capita income.